When Avatars Teach Geography: Evaluating a Metaverse-Based Geosite Ecosystem for Spatial Thinking in High School Physical Geography - Laksono Dwi Nugroho; Khoirul Habibah; Anita Kumala Dewi; Siska Maulidhin Hidayah (CV Bumi Spasial, 2026)
Traditional text-based instruction frequently struggles to visualize abstract lithospheric threshold concepts and complex multi-scale geosite phenomena. To overcome this critical spatial accessibility barrier, this study developed and evaluated the Smart Geo-Education Ecosystem, an innovative metaverse-based social virtual reality platform engineered for high school physical geography instruction within the Ijen UNESCO Global Geopark. Guided by the iterative ADDIE development framework, the ecosystem integrates authentic geodetic data modeling via QGIS and Spatial.io web-based architectures. The research methodology utilized a robust quasi experimental design involving 140 geography students split into experimental and control cohorts, alongside comprehensive validation tests by specialized subject matter and media experts. Expert validation confirmed that the developed ecosystem is highly feasible for geography instruction, successfully resolving early content scaling misconceptions. Quantitatively, the efficacy of the platform was substantiated by a significant escalation in students' spatial thinking scores, surging from a baseline average of 59.38 in the control group to 80.35 in the experimental group. This cognitive advancement is statistically validated by an Independent Samples t-test value of 50.031 (p < 0.001), with a calculated Cohen’s d effect size indicating a high magnitude of pedagogical impact. Unlike traditional, solitary virtual tours, this platform establishes an avatar-mediated social VR environment that facilitates real-time interaction, synchronous joint attention, and collaborative spatial inquiry within a high-fidelity virtual landscape. The platform functions as an effective pedagogical scaffold that successfully bridges formal classroom-based instruction and asynchronous, autonomous exploration, offering a highly scalable, innovative template for global geography education.